Tunnel stability analysis of coral reef limestone stratum in ocean engineering. (1st December 2022) - Zhang, X.Y.; Zhang, L.W.; Wu, J.; Fu, H.; Dian, L.Y.
Abstract: The islands and coasts in the South China Sea have developed coral reefs, which are the basis for the development of ocean resources and the construction of ocean engineering. However, the biogenetic coral reef limestone in the sea has the physical properties of much porosity, low strength and low density, which is obviously different from the traditional geological rock mass during the underground engineering construction. So in this paper, surrounding rock stability of coral reef limestone stratum in tunnel excavation is studied by physical model tests and numerical simulation. Firstly, according to the similarity theory, quartz sand, barite powder, high strength gypsum, calcareous sand and cement are selected to configure the similar materials of coral reef limestone by the orthogonal ratio test and physical mechanics test. Secondly, the triaxial geomechanical model tests of tunnel excavation in coral reef limestone stratum are carried out. The influence of tunnel shape, support method and rock strength on the tunnel stability is studied by analyzing the variation laws of displacement and stress of the surrounding rock. Finally, the numerical calculation of tunnel excavation in coral reef limestone stratum is conducted and the results of physical model tests are verified. The influence of tunnel depth on the surrounding rock stability is further studied. The results show that: (i) Compared with the horseshoe shaped tunnel, the displacement of the circular tunnel at the haunch and springer is significantly increased, and the stress concentration phenomenon occurs. (ii) The stress release rate and displacement of surrounding rock decrease significantly when the anchor support is added or the strength of reef limestone increases. (iii) The stress release rate and displacement of surrounding rock increase with the tunnel depth, so the support strength of surrounding rock should be increased. Highlights: The similar materials of coral reef limestone are configured by the orthogonal ratio test and physical mechanics test. The triaxial geomechanical model tests of tunnel excavation in coral reef limestone stratum are carried out. The numerical calculation of tunnel excavation in coral reef limestone stratum is conducted. The physical model tests are verified by numerical calculation, and the influencing factors of tunnel stability are analyzed.